THE EXPECTED ROLE FOR WTO AGREEMENT ON THE APPLICATION OF SANITARY AND PHYTOSANITARY MEASURES IN SHEEP TRADE IN SUDAN - Ahmed Mohammed Elamin, Huyam; Eltayeb Ibrahim, Abdelaziz (Journal of Veterinary Medicine and Animal Production, 2022)
Data was collected from Port Sudan veterinary quarantine in the Red Sea from the annual and monthly reports during the period from 1999 to 2005. Information about international trade agreement were collected and discussed to explain the role of The World Trade Organization (WTO) and The Agreement on the application of Sanitary and Phytosanitary (SPS) measures, in regulating livestock trade and how these measures may act as a technical barrier to sheep trade. Results showed that about 4.4% to 14.5% from the monthly exports of sheep were rejected in the year 2005 due to sanitary measures, which may be used as a disguised restriction to trade.